“O que se faz, como se faz, por que se faz?” – focalizando o núcleo da terapia ocupacional no campo da saúde mental infantojuvenil - Táparo, Flávia Arantes (2023)
The field of child and youth mental health is understood as a multidisciplinary field, where different professional cores, including Occupational Therapy, interrelate, supporting each other in the fulfillment of theoretical and practical activities within this field. The available literature incipiently identifies the elements that characterize the professional core of Occupational Therapy in the field of child and adolescent mental health, pointing to the importance of deepening the knowledge in this theme. Thus, the present study had the general objective of identifying the perspective of occupational therapists involved in the psychosocial care of children and adolescents about the professional core of Occupational Therapy in the field of child and adolescent mental health. As specific objectives, the study sought to: identify aspects that support and/or influence the practices of occupational therapists in the field of mental health of children and adolescents; and analyze how other professionals involved in the psychosocial care of children and adolescents describe and evaluate the practice of occupational therapists in the field of child and adolescent mental health. An exploratory-descriptive study was carried out, with a qualitative and quantitative approach, in two phases. In Phase 1, 107 professionals participated, of which 59 were occupational therapists and 48 non-occupational therapists, who answered an online questionnaire. The questionnaire began with multiple-choice questions related to the sociodemographic aspects of the participants, followed by open questions about aspects and elements perceived about the core of Occupational Therapy in the field of child and youth mental health. In Phase 2 had the participation of 32 professionals who had participated in the first phase, of which 20 were occupational therapists and 12 non-occupational therapists. In this phase, four online focus groups were performed, two with each group of participants. The focus groups aimed to deepen the discussion about the professional core of Occupational Therapy in the field of child and adolescent mental health. The results of the sociodemographic evaluation, obtained with the questionnaire, were analyzed using descriptive statistics, while the data obtained in the open questions of the questionnaire and in the focal groups were analyzed using the Iramuteq® software. The results obtained with the sociodemographic questions of the questionnaire indicated a majority participation of cisgender women, occupational therapists and residents of the State of São Paulo. Among the non-occupational therapist participants, the participation of psychologists, nurses and social workers, respectively, stood out. Most of the participants were post graduated professionals and had previous experience working in Centers for Psychosocial Care (CAPS) for children and adolescents. The analysis of the results of the open questions of the questionnaire and of the focal groups, allowed answering the questions that appear in the title of this research. Regarding the question of what Occupational Therapy does and how it does in the field of child and adolescent mental health, the following were found: 1) the focus on occupations and on daily life activities; 2) the acting on routines and based on the daily lives of individuals; 3) the integral perspective on the subjects; 4) the weave of networks and intersectionality; 5) the acting on interface with the field of Education; 6) the acting in situations of intense psychic suffering and handling crisis situations; 7) the acting on situations of vulnerabilities and violence; and 8) the acting in the most serious and complex cases. As for why Occupational Therapy works in this way in this field , the results showed an approximation between the core of Occupational Therapy and the premises of psychosocial care of children and adolescents, which support the field of child and adolescent mental health, in the following aspects: 1) the importance of welcoming and listening; 2) valuing identities and subjectivities; 3) “doing together” what makes sense; 4) the expansion of autonomy and social participation; and 5) construction of life projects. The approximations between the core of Occupational Therapy and the field of child and adolescent mental health are the result of similar historical processes that this core and this field have gone through in the context of the Psychiatric Reform (especially Brazilian). They translate the unison and current theoretical understandings of both field and core in defense of childhoods and adolescences, of the care in a network setting and in freedom, the preservation of autonomy and citizenship and the appreciation of this population as active subjects and protagonists of their own history. It makes evident the importance and potency of the Occupational Therapy core in the field of child and youth mental health.